Melatonin and spermidine protect early mouse embryos from ethylparaben toxicity by restoring histone modifications and subcellular structures - Yong-feng Wang; Yu-ting Wan; Qing Tian; Ying Yin; Jia-wei Xu; Li-quan Zhou (Ecotoxicology and Environmental Safety)
Ethylparaben (EtP), a widely used preservative in food and cosmetics, has raised increasing concerns in the field of reproductive toxicology due to its potential adverse effects on human health. In this study, we show that EtP exposure induces developmental arrest at the 2-cell stage in mouse embryos. This arrest coincides with elevated reactive oxygen species levels, mitochondrial dysfunction, DNA damage, and apoptosis. Transcriptomic analysis reveals widespread gene dysregulation following EtP exposure, characterized by the downregulation of maternal-effect genes, cleavage-stage embryo genes, and mitochondria-associated genes. These downregulated genes are primarily involved in transcription activation and apoptosis, while upregulated genes are enriched in DNA damage response pathways. Furthermore, EtP exposure alters histone modifications in embryos, leading to impaired transcriptional activity. We find that melatonin and spermidine partially rescue the developmental arrest by mitigating oxidative stress. Together, our findings demonstrate that EtP exacerbates oxidative stress, disrupts mitochondrial integrity, and damages DNA in mouse embryos, ultimately impairing transcription and developmental progression. Notably, EtP-induced disruption of histone modifications compromises zygotic genome activation, resulting in embryonic arrest. In contrast, melatonin and spermidine alleviate oxidative damage and mitochondrial dysfunction, partially restoring normal embryonic development following EtP exposure.